Revaluation of aquaculture waste and by-products under a circular economy approach: systematic literature review - Coronado Guerrero, Renzo Gabiel; Márquez Sandoval, Carlos Alfonso (LACCEI, 2025)
Aquaculture has surpassed extractive fishing in global production, consolidating its position as a key sector for food security. However, this growth has increased the generation of solid and liquid waste, and by-products, whose inadequate management generates significant environmental impacts. This systematic literature review (SLR) analyzes current and emerging methods for revaluing aquaculture waste using a circular economy approach. Thirty scientific articles indexed in Scopus and Web of Science, published between 2020 and 2025, were examined. The methodology was structured using the PICO and PRISMA strategies, allowing for a rigorous and categorized selection. The findings show that the most common waste products include viscera, scales, shells, sludge, and effluents. Notable techniques include enzymatic hydrolysis, anaerobic digestion, aquaponics, multi-trophic systems (MTS), and ecological extraction processes. These allow for the recovery of compounds such as collagen, peptides, biogas, and biofertilizers. Unlike traditional methods, these technologies valorize waste as a productive input, reducing pollution and generating high-value-added products. Despite their benefits, many of these methodologies are still in the experimental phase, facing economic, technological, and regulatory limitations.The conclusion is that the implementation of these solutions can transform aquaculture waste into strategic resources, contributing to environmental sustainability, economic efficiency, and productive innovation in the sector.